THE EFFECT OF PEDAGOGICAL CONTENT KNOWLEDGE (PCK) LEARNING MANAGEMENT TOWARD LEARNING OUTCOMES THROUGH STUDENT LEARNING MOTIVATION IN PHYSICS - Aan Juhana Senjaya; Maman Rakhmanudin; Ipong Dekawati (Universitas Ahmad Dahlan, 2021)
Research on physics learning management has not been done much, especially regarding PCK and learning outcomes. Many studies that investigate the relationship between variables use the regression method. However, this study using path analysis. The purpose of this study was to measure the direct effect, indirect effect, and total effect of PCK, learning motivation, and student physics learning outcomes using path analysis. The research method used in this research is a survey with a quantitative approach and data analysis techniques, namely path analysis. The data collection technique used a closed questionnaire. This study's sample was 43 teachers who gathered from 64 high school physics teachers in Indramayu Regency. The PCK learning management research results had no significant effect on student learning outcomes. Learning motivation had a positive effect, and learning motivation had a positive effect on student learning outcomes. The implication of this study that the principal and the education office should continue to strive to improve the quality and smoothness of the teaching and learning process by providing provision to teachers to improve pedagogical content knowledge (PCK) learning management by participating in workshops and continuously improving techniques to motivate students for results student learning better.